2011
DOI: 10.1093/ageing/afr115
|View full text |Cite
|
Sign up to set email alerts
|

Improving recruitment of older people to research through good practice

Abstract: There is widespread evidence both of the exclusion of older people from clinical research, and of under-recruitment to clinical trials. This review and opinion piece provides practical advice to assist researchers both to adopt realistic, achievable recruitment rates and to increase the number of older people taking part in research. It analyses 14 consecutive recently published trials, providing the number needed to be screened to recruit one older participant (around 3:1), numbers excluded (up to 49%), drop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
203
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(216 citation statements)
references
References 27 publications
10
203
0
3
Order By: Relevance
“…Older adults may lack understanding of the study protocols, have lower levels of education and be unwilling to make a time commitment [32]. Furthermore, some older persons find research studies intrusive through excessive interviews or collection of biological samples [8].…”
Section: Discussionmentioning
confidence: 99%
“…Older adults may lack understanding of the study protocols, have lower levels of education and be unwilling to make a time commitment [32]. Furthermore, some older persons find research studies intrusive through excessive interviews or collection of biological samples [8].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced age, physical frailty, the presence of comorbidities and uncertainty about the future were also identified as reasons why some people may be reluctant to become involved in research. Age-related factors are recognised as a significant barrier to recruitment into trials 701,722 yet, in the proposed trial, the population pool from which recruits will be drawn will be largely > 70 years of age. Exclusion criteria related to comorbid conditions and previous malignancies may therefore need to be modified in the protocol if older and more frail patients are to be included in the research and for the trial results to be externally valid.…”
Section: Squamous Cell Skin Cancer Work Programmementioning
confidence: 99%
“…In addition, the patient must not appear to object to take part, and the welfare of the patient must always be placed above the importance of the research and confirmed by an appointed third party [54][55][56][57]. Although this process can appear so resource-and time-intensive as to inhibit the conduct of research involving the elderly, this has been found not necessarily to be the case, provided provision is made for the inherent difficulties anticipated [58,59].…”
Section: Involving Older Patients In Researchmentioning
confidence: 99%